Rugopharynx australis (Nematoda: Strongyloidea) Infection in Captive Red Kangaroos (Osphranter rufus) in Bulgaria: A Case Report - Mariana Panayotova-Pencheva; Joanna Banasiewicz; Anna Maria Pyziel (Journal of Zoological and Botanical Gardens)
Faecal parasitological examination of three red kangaroos (Osphranter rufus) newly arrived at Sofia Zoo, Bulgaria, revealed infestation with nematode eggs. The animals were successfully treated with albendazole and ivermectin. Adult nematodes obtained after deworming the kangaroos were identified as gastric strongylids of the species Rugopharynx australis (Mönnig, 1926). The initially collected faecal samples were used to follow the development of the parasites, in particular, the viability of the larvae hatching from the eggs. Morphometric and molecular data as well as some epidemiological observations of the species in the present materials are provided. The study provides the first morphological description of the free-living, infective third-stage larvae of the species. It is also the first record of R. australis in captive-bred kangaroos on the European continent.